Transformasi Akad Mudharabah: Produk Tabungan Syariah di Tengah Inovasi Digital dan Literasi Finansial - Ummah, Ina Nasihatul (TAWAZUN: Journal of Sharia Economic Law, 2026)
The transformation of the mudharabah contract in Islamic savings products reflects an alignment between the principles of Islamic jurisprudence (fiqh muamalah) and the demands of a modern financial system. This article examines the legal status of the mudharabah contract implemented in digital Islamic banking products, the normative gap between classical fiqh, DSN-MUI fatwas, and OJK regulations, as well as the legal implications of its transformation for the protection of depositors. Using normative legal research (normative legal research) with statutory, conceptual, and comparative approaches, this study identifies three major legal issues in the transformation of the mudharabah contract: the inclusion of collateral requirements, the application of fixed flat profit-sharing, and unilateral risk allocation to customers. The study finds that DSN-MUI Fatwa No. 115/DSN-MUI/IX/2017 and POJK No. 24/POJK.03/2015 partially bridge this gap, but normative gaps remain—particularly regarding the legal validity of digital contracts (e-contract), the transparency obligations of banks in digital profit-sharing disclosure, and the legal basis for consumer protection in digital mudharabah contracts. Financial literacy is identified as a non-legal but structurally significant factor in ensuring the alignment of contracts with practice.